High-temperature-resistant porous membrane material and preparation method thereof

By combining electrospinning and emulsion method, a high-temperature-resistant porous film material was prepared, which solved the problem of insufficient absorption capacity of the existing electromagnetic wave absorption film, achieved efficient and lightweight wave absorption performance, and reduced production costs.

CN119433995AActive Publication Date: 2025-02-14BEIJING INST OF ASTRONAUTICAL SYST ENG +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411394295.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-14
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing electromagnetic wave absorption film has insufficient wave absorption capacity, especially in high temperature environments, it is difficult to effectively absorb electromagnetic waves.

Method used

High-temperature resistant nanofibers were prepared by electrospinning, and highly oriented composite fibers were prepared by spinning. Absorbing particle modified silicone resin nanoemulsion was prepared by combining a one-step emulsion method. After soaking and curing, a rough and magnetic surface was formed. Porous nanocolumns were finally prepared to produce shock-resistant and high-temperature-resistant porous films.

Benefits of technology

It significantly improves wave absorption capacity. The material is not only heat insulation and high temperature resistance, but also has strong wave absorption performance. It is suitable for a wide range of application scenarios, and simplifies the traditional cutting and grinding process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433995A_ABST
    Figure CN119433995A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant porous membrane material and a preparation method thereof, and belongs to the technical field of preparation of wave-absorbing materials. In order to solve the problem that the wave absorbing capacity of an electromagnetic wave absorbing film is insufficient, the method comprises the steps that a high-temperature-resistant fiber precursor is prepared through an electrostatic spinning technology, and high-temperature-resistant nanofibers are obtained through heat treatment at high temperature; blending the nanofibers with a polymer, and preparing composite fibers with highly-oriented nanofibers through spinning; the composite fibers are bundled and subjected to pressurized pyrolysis treatment at high temperature, and oriented nanofiber bundles are obtained; preparing a wave-absorbing particle modified silicon resin nano-emulsion by adopting a one-step emulsion method; the oriented nanofiber bundle is soaked in the wave-absorbing particle modified silicon resin nano emulsion, and after full infiltration, the oriented nanofiber bundle is taken out and dried; and heating and curing step by step according to a modified silicon resin curing process to obtain the porous nano-cylinder. According to the method, the wave absorbing capacity is greatly improved. The porous membrane not only insulates heat, but also resists high temperature, and is strong in wave-absorbing capacity and very wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing wave-absorbing materials, and in particular relates to a high-temperature resistant porous membrane material and a preparation method thereof. Background Art

[0002] With the development of science and technology, electromagnetic waves are increasingly used and have penetrated into every aspect of our lives. However, while electromagnetic waves bring convenience, they also bring many challenges, such as electromagnetic radiation pollution and electromagnetic interference. With the explosive growth of electronic equipment and wireless communication facilities, electromagnetic pollution is becoming increasingly serious, which not only affects the daily operation of equipment, but also brings harm to human production activities. Therefore, how to effectively absorb and reduce the negative impact of electromagnetic waves has become an important topic in the current scientific research field. Especially in the field of aerospace, low-density, high-temperature resistant absorbing materials are particularly important.

[0003] The low-density, high-temperature resistant electromagnetic wave absorbing film is a special film material. It is light and strong, and can work stably in high-temperature environments and effectively absorb electromagnetic waves. The research and development of this film integrates the wisdom of multiple disciplines such as materials science, electromagnetism, and chemistry. Its preparation process involves complex chemical reactions and physical processes. By precisely controlling the proportion of raw materials and reaction conditions, an absorbing film with excellent performance can be obtained. In the composition of the high-temperature resistant electromagnetic wave absorbing film, the micro-nano array structure and the absorbing filler are the core components. On the one hand, the multi-level reflection effect of the micro-nano array structure is used to improve the absorption of electromagnetic waves; on the other hand, the physical absorption and structural design of the absorbing filler are used to achieve efficient absorption of broadband electromagnetic waves by regulating the dielectric constant and stroboscopic characteristics. In addition, the electromagnetic wave absorbing film also has the characteristics of high absorption, good compatibility, and large dielectric loss, so that the electromagnetic waves are effectively converted into thermoelectric energy inside the film layer and consumed by electron scattering, energy conduction or low-frequency radiation of electromagnetic waves.

[0004] In addition to its excellent wave-absorbing performance, the electromagnetic wave absorbing film also has excellent high-temperature resistance. It can remain stable in a high-temperature environment of up to 1500°C without falling off or cracking, ensuring the long-term and effective wave-absorbing function of the coating. This feature makes the high-temperature resistant electromagnetic wave absorbing film have broad application prospects in high-temperature equipment, aerospace and other fields. With the continuous development of science and technology, high-temperature resistant electromagnetic wave absorbing coatings and their coating technology will continue to be optimized and improved. In the future, we can expect this coating to be used in more fields, bringing more convenience and safety to people's lives. At the same time, we should also pay attention to the new problems and challenges that may arise during its application, and continue to explore solutions to promote the continuous progress and development of this technology. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of insufficient wave absorption capacity of electromagnetic wave absorption film, and to provide a high-temperature resistant porous membrane material and a preparation method thereof. The method constructs a nano-array light trap, takes a new type of nano-array porous membrane as a carrier, utilizes its regular and orderly nano-pores to load high-absorbing materials, adjusts electromagnetic parameters, improves the impedance matching degree and improves the dispersion, so as to obtain a lightweight and efficient wave-absorbing membrane material. On the one hand, the reflection of light on the membrane surface can be weakened, and on the other hand, the light entering the nano-pores can be reflected and absorbed multiple times on the pore surface, achieving an attenuation effect, thereby greatly enhancing the wave absorption characteristics.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a high temperature resistant porous membrane material, the method comprising:

[0008] (1) preparing a high temperature resistant fiber precursor by an electrospinning process, and heat treating the fiber precursor at a high temperature to obtain a high temperature resistant nanofiber;

[0009] (2) blending the high temperature resistant nanofibers with polymers (the polymer accounts for 60% to 99.99%), and preparing composite fibers with highly oriented nanofibers by spinning;

[0010] (3) bundling the composite fibers and subjecting them to pressure pyrolysis treatment at high temperature to obtain oriented nanofiber bundles;

[0011] (4) preparing the microwave-absorbing particle-modified silicone resin nanoemulsion by a one-step emulsion method;

[0012] (5) immersing the oriented nanofiber bundle in the microwave-absorbing particle-modified silicone resin nanoemulsion, and after being fully absorbed and infiltrated, taking it out and drying it;

[0013] (6) The modified silicone resin is cured by step-by-step temperature increase to obtain a porous nanocolumn with a rough surface and magnetic properties.

[0014] (7) Cutting the porous nanorods according to the required size requirements to obtain an impact-resistant and high-temperature resistant microwave-absorbing porous membrane.

[0015] Furthermore, in step (1), the high temperature resistant fiber is one or a combination of glass fiber, basalt fiber, asbestos fiber, metal fiber, boron nitride fiber, ceramic fiber, carbon fiber, and graphite fiber.

[0016] Furthermore, in step (1), the electrospinning conditions are: spinning solution concentration 0.5% to 30%, voltage 1 to 100 kV. The spinning solution is a mixture of high temperature resistant fiber precursor particles and a solvent. The solvent is one of dimethyl sulfoxide, tetrahydrofuran, ethanol, methanol, acetic acid, ether, ethylene glycol, acetone, acetonitrile, phenol, and methanesulfonic acid, or a mixture thereof.

[0017] Furthermore, in step (1), the heat treatment temperature is 20 to 3000° C., and the time is 0.1 to 72 hours.

[0018] Furthermore, in step (2), the polymer is one or more of polyethylene, polypropylene, polyethylene terephthalate, phenolic resin, epoxy resin, polyurethane, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene glycol, polyamide, and cellulose.

[0019] Furthermore, in step (2), the high temperature resistant nanofibers and the polymer are blended by solvent blending or melt blending. Correspondingly, if the blending is melt blending, the spinning is melt spinning; if the blending is solution blending, the spinning is solution spinning; the temperature of the melt blending is 50 to 400°C.

[0020] Furthermore, in step (2), the solvent blended is one of acetone, ethanol, methanol, ethylene glycol, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, dichloromethane, chloroform, phenol, paraffin oil, or a mixed solvent. Most of the solvent blending does not require heating, but some systems require heating, with a maximum temperature of no more than 260°C.

[0021] Furthermore, in step (3), the high temperature and pressure pyrolysis treatment conditions are: pressure 0.1-20 MPa, temperature 20-1000° C., and time 0.1-24 h; in step (6), the stepwise temperature curing is specifically: 200-300° C. for curing for 1-3 h, 400-500° C. for curing for 1-2 h, and 600-800° C. for curing for 0.1-1 h.

[0022] Furthermore, in step (4), the one-step emulsion method is as follows: adding the absorbing particle-modified silicone resin to an aqueous phase containing 10 wt % of an emulsifier and 15 wt % of a dispersant at a rate of 1 to 10 drops per second, stirring at a speed of 100 to 10,000 rpm, and stirring for 1 to 60 minutes; the concentration of the absorbing particle-modified silicone resin is 0.5 to 50 wt %.

[0023] Furthermore, in step (4), the absorbing particles are one or more of graphite, graphene, carbon black, carbon fiber, carbon nanotubes, ferrite, iron oxide, magnetic iron nanomaterials, silicon carbide, conductive polymers, chiral materials, and plasma materials. The absorbing particles and the silicone resin are stirred and dispersed at a high speed in a mass ratio of 5:95 to 45:55 to obtain the absorbing particle modified silicone resin.

[0024] A high temperature resistant porous membrane material prepared by the above preparation method.

[0025] The beneficial effects of the present invention compared to the prior art are:

[0026] (1) This method can prepare highly ordered nanowire array structures, greatly improving the microwave absorption capability.

[0027] (2) The porous membrane is not only heat-insulating, but also resistant to high temperatures and has strong wave absorption capabilities, and has a very wide range of adaptability.

[0028] (3) Through the programmed arrangement and sintering of nanowires, the preparation of special-shaped curved membrane materials can be easily achieved, which greatly reduces the quality problems caused by traditional cutting and grinding and saves costs.

[0029] (4) The process is simple and feasible, and can be easily prepared on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the precursor structure;

[0031] Figure 2 Schematic diagram of the precursor structure obtained by electrospinning;

[0032] Figure 3 Schematic diagram of nanofibers obtained by high temperature treatment;

[0033] Figure 4 Schematic diagram of nanofiber / polymer blend;

[0034] Figure 5 is a schematic diagram of nanofiber / polymer fiber;

[0035] Figure 6 Schematic diagram of nanofiber / polymer fiber bundling;

[0036] Figure 7 Schematic diagram of the high temperature pyrolysis structure of nanofiber / polymer bundle fiber;

[0037] Figure 8 Schematic diagram of the structure of magnetic particles attached to the surface of high-temperature cracking bundled fibers;

[0038] Fig. 9 It is a schematic diagram of the division from the absorbing block to the membrane material;

[0039] Fig.10 This is the morphology of the ceramic nanofiber in Example 1;

[0040] Fig.11 This is a diagram showing the internal structure of the ceramic nanofiber / polymer composite fiber in Example 1;

[0041] Fig.12 This is a diagram of the ceramic nanofiber / polymer composite fiber bundle structure in Example 1;

[0042] Fig.13This is a morphology of the microwave-absorbing particles attached to the ceramic nanofiber / polymer composite fibers after being bundled in Example 1;

[0043] Fig.14 This is the surface morphology of the ceramic film after cutting in Example 1. DETAILED DESCRIPTION

[0044] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0045] Embodiment 1:

[0046] (1) Add 90g aluminum powder and 10g aluminum chloride to 200g deionized water, stir and reflux the mixture at 60-100°C, add 5g cryolite, continue stirring for 12-48 hours, and age the resulting solution at 50-120°C until the viscosity reaches 1-5000Pa·s to obtain an electrospinning precursor. Alumina ceramic fiber precursor was prepared by electrospinning at 20kV, and the fiber precursor was heat treated at 1300°C for 3h to obtain high temperature resistant nanofibers, such as Fig.10 As shown;

[0047] (2) blending ceramic fiber with polyethylene terephthalate (mass ratio 20:80), and preparing ceramic fiber highly oriented polyethylene terephthalate composite fiber by melt spinning at 285°C;

[0048] (3) The highly oriented polyethylene terephthalate composite fiber bundles were compressed to 5 MPa and 800 °C for 4 h to obtain oriented ceramic nanofiber bundles, such as Fig.12 As shown;

[0049] (4) 10 g of iron oxide particle-modified silicone resin (mass ratio 5:95) was added dropwise at a rate of 2 drops / second to an aqueous phase containing 10 wt % of an emulsifier and 15 wt % of a dispersant, with a stirring speed of 2000 rpm for 30 minutes to obtain an iron oxide particle-modified silicone resin emulsion;

[0050] (5) immersing the oriented ceramic nanofiber bundle in the iron oxide particle modified silicone resin emulsion, adsorbing and soaking for 0.4 h, and then taking it out to dry, the drying conditions are normal pressure, 120 ° C, and 2 h;

[0051] (6) According to the modified silicone resin curing process, the curing is performed step by step at a temperature rise of 220°C for 2 h, 450°C for 1.5 h, and 700°C for 0.3 h, to obtain a porous nanocolumn with a rough surface and magnetic properties, such as Fig.13 As shown;

[0052] (7) Cutting the porous nanorods according to the required size requirements to obtain impact-resistant and high-temperature resistant microwave absorbing porous membranes, such as Fig.14 shown.

[0053] The obtained absorbing porous membrane has a compression strength of 123 MPa at room temperature in the thickness direction, a compression strength of 54 MPa at 800°C, a porosity of 82.3%, an absorption of 30 MHz to 18 GHz ≥ 15 dB, and a high temperature resistance of ≥ 1000°C.

[0054] Embodiment 2:

[0055] (1) Add 50g of boric anhydride and 10g of tricalcium phosphate to 320g of deionized water, stir and reflux the mixture at 60-100°C to obtain an electrospinning precursor. Blend with 10g of alumina and 4.8h of ammonium chloride, prepare an alumina boron nitride fiber precursor by an electrospinning process at a voltage of 12kV, nitridate the fiber precursor in ammonia, treat at 300°C for 2h, 800°C for 3h, and heat treat at 1300°C for 3h to obtain high temperature resistant boron nitride nanofibers;

[0056] (2) blending boron nitride fiber with polyethylene (mass ratio 25:75) and preparing boron nitride fiber-polyethylene composite fiber with high orientation by melt spinning at 170°C;

[0057] (3) The highly oriented boron nitride fiber and polyethylene composite fiber are bundled, pressurized at 3 MPa, and 800 °C for 4 h to obtain oriented boron nitride nanofiber bundles;

[0058] (4) 10 g of iron oxide particle-modified silicone resin (mass ratio 5:95) was added dropwise at a rate of 2 drops / second to an aqueous phase containing 10 wt % of an emulsifier and 15 wt % of a dispersant, with a stirring speed of 2000 rpm for 30 minutes to obtain an iron oxide particle-modified silicone resin emulsion;

[0059] (5) immersing the oriented boron nitride nanofiber bundle in the iron oxide particle modified silicone resin emulsion, adsorbing and soaking for 0.4 h, and then taking it out to dry, the drying conditions are normal pressure, 120 ° C, and 2 h;

[0060] (6) performing step-by-step temperature curing according to the modified silicone resin curing process, wherein the step-by-step temperature curing conditions are: curing at 220° C. for 2 h, curing at 450° C. for 1.5 h, and curing at 700° C. for 0.3 h, to obtain a porous nanocolumn with a rough surface and magnetic properties;

[0061] (7) Cutting the porous nanorods according to the required size requirements to obtain an impact-resistant and high-temperature resistant microwave-absorbing porous membrane.

[0062] The obtained absorbing porous membrane has a compression strength of 77 MPa at room temperature in the thickness direction, a compression strength of 24 MPa at 800°C, a porosity of 89.1%, an absorption of 30 MHz to 18 GHz ≥ 11 dB, and a high temperature resistance of ≥ 1260°C.

Claims

1. A method for preparing a high temperature resistant porous membrane material, characterized in that: The method is: (1) preparing a high temperature resistant fiber precursor by an electrospinning process, and heat treating the fiber precursor at a high temperature to obtain a high temperature resistant nanofiber; (2) blending the high temperature resistant nanofibers with polymers (the polymer accounts for 60% to 99.99%), and preparing composite fibers with highly oriented nanofibers by spinning; (3) bundling the composite fibers and subjecting them to pressure pyrolysis treatment at high temperature to obtain oriented nanofiber bundles; (4) preparing the microwave-absorbing particle-modified silicone resin nanoemulsion by a one-step emulsion method; (5) immersing the oriented nanofiber bundle in the microwave-absorbing particle-modified silicone resin nanoemulsion, and after being fully absorbed and infiltrated, taking it out and drying it; (6) Performing step-by-step temperature curing according to the modified silicone resin curing process to obtain porous nanocolumns.

2. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (1), the high temperature resistant fiber is one or a combination of glass fiber, basalt fiber, asbestos fiber, metal fiber, boron nitride fiber, ceramic fiber, carbon fiber, and graphite fiber.

3. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (1), the electrospinning conditions are: spinning solution concentration 0.5% to 30% and voltage 1 to 100 kV.

4. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (1), the heat treatment temperature is 20 to 3000° C. and the time is 0.1 to 72 hours.

5. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (2), the polymer is one or more of polyethylene, polypropylene, polyethylene terephthalate, phenolic resin, epoxy resin, polyurethane, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene glycol, polyamide, and cellulose.

6. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (2), the high temperature resistant nanofibers and the polymer are blended by solvent blending or melt blending. Correspondingly, if the blending is melt blending, the spinning is melt spinning; if the blending is solution blending, the spinning is solution spinning; the temperature of the melt blending is 50 to 400°C.

7. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (3), the high temperature and pressure pyrolysis treatment conditions are: pressure 0.1-20 MPa, temperature 20-1000°C, and time 0.1-24 h; in step (6), the stepwise temperature curing is specifically: 200-300°C curing for 1-3 h, 400-500°C curing for 1-2 h, and 600-800°C curing for 0.1-1 h.

8. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (4), the one-step emulsion method is as follows: adding the absorbing particle-modified silicone resin to an aqueous phase containing 10 wt % of an emulsifier and 15 wt % of a dispersant at a rate of 1 to 10 drops per second, stirring at a speed of 100 to 10,000 rpm for 1 to 60 minutes; the concentration of the absorbing particle-modified silicone resin is 0.5 to 50 wt %.

9. The method for preparing a high temperature resistant porous membrane material according to claim 1, characterized in that: In step (4), the absorbing particles are one or more of graphite, graphene, carbon black, carbon fiber, carbon nanotubes, ferrite, iron oxide, magnetic iron nanomaterials, silicon carbide, conductive polymers, chiral materials, and plasma materials.

10. A high temperature resistant porous membrane material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hybrid modified composite material with high-conductivity and high-toughness structure and preparation method of hybrid modified composite material

    CN106671525A

  • Preparation method and application method of three-dimensional porous graphene functionalized assembly membrane material

    CN106943896A

  • Light efficient wave-absorbing material SnFe2O4 / C composite nanofiber, wave-absorbing coating and preparation method

    CN112391833A

  • Candida-like wave-absorbing material and preparation method thereof

    CN118516845A